Optimisation of waqf contribution awareness among Indonesian workers through digital system / Ruslan A Ghofur ... [et al.] - Ghofur, Ruslan A; Madnasir; Anggraini, Erike; Nurlaili; Mohd Abas 2, Mohd Khalid (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2023)
The use of digital system has penetrated various levels of society, including the Indonesian Workers (TKI) in Malaysia. This qualitative study is based on community service was conducted in Kampong Bahru, Kuala Lumpur, because it is the centre of activity for TKI communities in Malaysia. Kampong Bahru is an area in Kuala Lumpur, Malaysia, that has high population of Indonesian workers. In this context, waqf contribution optimisation can play an important role in improving TKI welfare livelihood and also helps the development of Sharia-based economy among the TKI community. The awareness about waqf contribution using digital system among Indonesian workers in Malaysia is still low. The Asset Based Community Development (ABCD) method was used in the study. The ABCD stages conducted are preparation, seminars, workshops, mentoring, and evaluation. Outcome of this research suggested that there is an increase in the waqf awareness and waqf contribution through digital system and designing a waqf scheme among TKI. The digital waqf system can be accessed through using an online banking system.